Evaluasi dan Supervisi Klinis : Konsep, Implementasi, dan Tantangan - Kristanti Olivia; Dessy Eka Citra Dewi (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Clinical evaluation and supervision are two crucial elements in improving the quality of learning and professional practice, especially in the fields of education and health services. Evaluation serves as a tool to assess performance, effectiveness, and achievement of learning or service objectives, while clinical supervision emphasizes the process of mentoring, coaching, and competency development through a reflective and collaborative approach between supervisors and supervised individuals. In practice, the implementation of clinical evaluation and supervision faces various challenges, ranging from limited competent human resources, lack of understanding of the concept and purpose of correct supervision, to resistance from the supervised. However, with the right approach and ongoing training, clinical evaluation and supervision can be an effective means of building a professional work culture, improving service quality, and creating a supportive learning environment. This study aims to comprehensively describe the basic concepts, implementation strategies, and main obstacles in clinical evaluation and supervision, in order to provide policy recommendations and best practices in the field.